2011
DOI: 10.1007/s00345-011-0809-6
|View full text |Cite
|
Sign up to set email alerts
|

Value of enhanced transrectal ultrasound targeted biopsy for prostate cancer diagnosis: a retrospective data analysis

Abstract: The combined use of CE-TRUS and RTE is feasible and allows for targeted biopsy and may improve PCa detection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(39 citation statements)
references
References 20 publications
3
36
0
Order By: Relevance
“…In contrast, multiparametric MRI reveals structural and tissue perfusion information. The usefulness of combining RTE with contrast-enhanced ultrasound has been found in previous studies [6,22].…”
Section: Discussionmentioning
confidence: 91%
“…In contrast, multiparametric MRI reveals structural and tissue perfusion information. The usefulness of combining RTE with contrast-enhanced ultrasound has been found in previous studies [6,22].…”
Section: Discussionmentioning
confidence: 91%
“…Because of encouraging technical innovations and developments in prostate imaging, it is now possible to visualise PCa with high sensitivity [7, 8]. Beside PCa localisation, modern imaging modalities are capable of providing information about tumour volume, local staging, and cancer aggressiveness, which may be helpful for choosing the most appropriate therapy [8, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Beside PCa localisation, modern imaging modalities are capable of providing information about tumour volume, local staging, and cancer aggressiveness, which may be helpful for choosing the most appropriate therapy [8, 9]. …”
Section: Introductionmentioning
confidence: 99%
“…Using a multiparametric targeted biopsy approach Aigner et al observed that the overall 59.4% PC detection rate (70 of 133 cases) was superior to that of a systematic approach. 26 Combining RTE and CEUS in our study significantly decreased the false-positive results of RTE alone from 34.9% to 10.3% and thereby improved the positive predictive value to 89.7% to correctly identify histopathologically confirmed PC in defined TLs. Although there was a trend toward higher Gleason patterns in hyperperfused TLs in our study, statistical analysis did not attain significance to assign a Gleason score to a hypoperfused or hyperperfused imaging pattern in our pilot study.…”
Section: Discussionmentioning
confidence: 76%